Puerto Rico : isle of enchantment - Owings, Lisa (Minneapolis, MN Bellweather Media, 2014)
"Developed by literacy experts for students in grades three through seven, this book introduces young readers to the geography and culture of Puerto Rico"--Provided by publisher.
Where is Puerto Rico? -- History -- The land -- El Yunque National Forest -- Wildlife -- Landmarks -- San Juan -- Working -- Playing -- Food -- Festivals -- The Taino -- Fast facts.
NC860L
Keywords: Puerto Rico